Caracterización de Aceites Esenciales en Especies Vegetales de la Familia Labiaceae de la Región La Libertad y Estudio de su Actividad Antibacteriana in vitro - Vigo Alcántara, Segundo Santiago (2005)
Essential oils were isolated from Satureja sericeae, “muña” and Mintosthachys tomentosa, “shalgarromero”, by steam distillation in yields of 0,12 and 0,14, respectively. The gas chromatogram of Satureja sericeae oil shows 29 different compounds, 23 of them were identified by mass spectrometry, the principal components being trans-caryphyllene (18,3 %), pulegone (12,6 %) and p-cymene (8,27 %). 32 different compounds were detected In Mintosthachys tomentosa oil, 26 of them were identified by mass spectrometry. The principal components in Mintosthachys tomentosa oil are 1,7,7-trimethyl-bicyclo[2.2.1]heptan-2-ol (10,1 %), endobornyl acetate (9,7 %) and 6,6-dimetil-bicyclo[3.1.1]hept-2-eno-carboxaldehído (7,6 %). Eight compounds common to both oils were identified. The IR spectra of both oils show hydroxyl and carbonyl groups, as well as carbon–carbon double bonds, which is coherent with the GC/MS results. However the Mintosthachys tomentosa oil shows a higher content of carbonylic compounds. The aromatogram of Estafilococcus aureus, β- hemolytic Estreptococcus and Klebsiella sp shows that these microorganisms are sensible to both essential oils .